Enhancing shared governance in Malaysian public universities - Asimiran, S.; Hussin, S. (2007)
Governance is linked to the distribution and exercise of power and authority, legitimately to a group of individuals through relevant laws for purposes of ensuring the growth, development, and sustainability of the institution. In many ways, shared governance emerged as a better mechanism in the governance of universities. Sharing of power, groups' interactions, negotiations, persdasions and mediations are essential to explain the process of university governance. Adopting the qualitative paradigm, this paper discusses the findings from a study conducted on power distribution and exercised of powers and authorities by the University Board of Directors and university top management in the governance of public universities in Malaysia. In-depth interviews through semi-structured questionnaires and document analysis formed a major part of the study. Powers and authorities were eminent issues raised by those interviewed and it was pointed out that through shared governance, the process of governing the universities could lead to good university governance. The governance process which worked through functional representation created by virtue of the Constitution, Statute or regulations was described as the most suitable mechanism in governing the Malaysian pUblic universities. The idea of having various representations was to have a system of check and balance and governance should result from cooperation, shared responsibility and mutual understanding among the various groups. We suggested a model of shared governance which draws on university's strengths to drive institutional directions within the legalized framework set by the University Constitution.